A head doesn't have a political gender - Picado León, Hugo Ernesto (2017)
This paper reviews the change proposes by the Electoral Supreme Tribunal in the resolution n.º 3603-E8-2016 regarding the scope of the application of horizontal parity in the list of the candidates to the Legislative Assembly in 2018 Elections. It also intends to elucidate possible partisan behavior because of this new juris-prudence.